1998
DOI: 10.1364/ao.37.000798
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy in the absorption and scattering spectra of chicken breast tissue

Abstract: Oblique incidence reflectometry is a simple and accurate method for measuring the absorption and the reduced-scattering coefficients of turbid media. We used this technique to deduce absorption and reduced-scattering spectra from wavelength-resolved measurements of the relative diffuse reflectance profile of white light as a function of source-detector distance. In this study, we measured the absorption and the reduced-scattering coefficients of chicken breast tissue in the visible range ͑400 -800 nm͒ with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
134
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 199 publications
(158 citation statements)
references
References 16 publications
18
134
1
1
Order By: Relevance
“…The measured penetration depth for 1/e decay in chicken breast tissue is approximately 1.16 cm, which matches well with the value reported in the literature (approx. 1.13 cm) at an optical wavelength of 650 nm [15]. The 5 cm penetration depth (approx.…”
Section: Resultsmentioning
confidence: 99%
“…The measured penetration depth for 1/e decay in chicken breast tissue is approximately 1.16 cm, which matches well with the value reported in the literature (approx. 1.13 cm) at an optical wavelength of 650 nm [15]. The 5 cm penetration depth (approx.…”
Section: Resultsmentioning
confidence: 99%
“…On one hand, an increase in sarcomere length can alter the scattering phase function and scatter more light toward fiber orientation [22]. On the other hand, the decrease in fiber diameter may reduce the scattering cross section [15], which reduced the probability that light being scattered away from the fiber orientation. More studies are necessary to elucidate the detailed mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the inherent fibrous structure, light propagation in muscle is anisotropic [14], and optical properties of muscle depend on measurement orientation [15,16]. More importantly, our recent studies [17] have found that light scattering in bulk muscle is strongly affected by sarcomere structure.…”
Section: Introductionmentioning
confidence: 99%
“…5 The thicknesses of the rear tissue T 1 and the front tissue T 2 , were approximately 3 and 4.5 mm, respectively. The reference point was created by placing a pinhole with an adjustable aperture at a short distance (22 mm) behind tissue T 2 , between T 2 and the MLAs.…”
Section: ͑1͒mentioning
confidence: 91%